PENGARUH GAYA KEPEMIMPINAN DAN EFEKTIVITAS KOMUNIKASI TERHADAP KINERJA KARYAWAN PDAM TIRTA KAMPAR - Rio Firmansyah; Susi Hendriani; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Water Company (PDAM) Tirta Kampar, which was established by Regulation Kampar District Regional Level II No. 02 of 1990 dated April 13, 1990 which authorized the governor of the Province of Riau with decision No. 02 of 1993, has the goal to serve the public interest in the field of provision of clean water in Kampar. While the function of the Regional Water Company (PDAM) Tirta Kampar is to seek the provision of clean water for the needs of people in Kampar. In an effort to improve employee performance PDAM Tirta Kampar, it would require a driving factor that can stimulate the spirit of the work in order to achieve company goals. The research was done in PDAM Tirta. While the purpose of this study was to determine the effect of leadership style and effectiveness of communication to employee performance at PDAM Tirta Kampar. The analysis model is a linear analysis with independent variables that leadership style and effectiveness of communication and the dependent variable is the performance of employees. While the number of respondents in this study were 61 respondents and sampling using census techniques. Based on the results of this study concluded that the variables of leadership style and effectiveness of communication has a significant influence either partially or simultaneously to employee performance PDAM Tirta Kampar. Test the correlation coefficient (R) independent variable on the dependent variable 0.931, which means there is a very strong relationship closeness while the test coefficient of determination (R2) of the independent variables on the dependent variable is 86.6%, while the remaining 13.4% influenced by other variables.Keywords: Performance, Style Leadership, Communication Effectiveness